ʼAṃʹ phvayʻ thvatʻ khoṅʻ Lvayʻ Mokʻ Toṅʻ kha rīʺ cañʻ - Moṅʻ Hanʻ, Muiʺ kutʻ (Kambhā luṃʺ Cā pe, 1994)
Journey of a Burmese writer to Lvayʻ Mokʻ Toṅʻ Cetī, a Buddhist shrine in Kolaṅʻʺ (Collin), Burma; includes history of the shrine.